Interpersonal Communication of Tourism Awareness Group in Increasing the Quality of Tourism Village Products: A study from Petarangan Village, Temanggung - Retno Budi Wahyuni; Warta Sumirat; Zulhelfa; Nuraeni Handayaningrum (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2023)
One tourist village in the Temanggung Regency area is the Petarangan tourist village. The beginning of the establishment of this tourist village was due to seeing the tourism potential there. The development to become a tourism village begins with a potential analysis in 2021, and then the local tourism authority will assess the village in 2022. The tourism awareness group (Pokdarwis) has a positive view of the community about how the activities their members carry out can influence people to start participating in it as an effort to care for tourism in Petarangan Village. The research finds out how interpersonal communication from Pokdarwis could increase the quality of tourism village products. Using a descriptive qualitative method focuses on the phenomenon of interpersonal communication used by stakeholders in that village. Data was taken by using questionnaires, interviews and checklists. All data were analyzed descriptively by considering the data validity through triangulation. The activities are about how the stakeholders communicate about the activities to develop the product. The medias used are electronic media and printed media. The message is almost about asking all stakeholders to participate. The role of Pokdarwis members is to get more members. So, community power plays an important role. It was found that interpersonal among the pokdarwis, stakeholders and community have been suitable for Pokdarwis in developing their tourism products.